Enforcement of FRAND Commitments under Article 102 TFEU The Nature of FRAND Defence in Patent Litigation - Väisänen, Tuire Anniina (Munich Intellectual Property Law Center - MIPLC, 2011)
Defining the true meaning of the acronym FRAND reminds of the parable of two political parties arguing before the elections: who is right and who is wrong, although they both know that there is no such thing as one truth and most utterly it depends on the individual perspective. Given the very substantial legal and business concerns involved within the telecommunication standardization environment, the conflicts what FRAND terms and conditions means seem to be unavoidable.